Recurrence in early breast cancer: Analysis of data from 3, 765 Australian women treated between 1997 and 2015. (April 2019) - Stuart-Harris, Robin; Dahlstrom, Jane E.; Gupta, Ruta; Zhang, Yanping; Craft, Paul; Shadbolt, Bruce
Abstract: Background: Evidence suggests recent improvements in outcome in early breast cancer (EBC). Aim: To analyse recurrence in women with EBC from our region from 1997 to 2015. Methods: We analysed recurrence in 3, 765 women with EBC. Median follow up was 83·0 months. 62·5% had a symptomatic presentation. 81·8% were hormone receptor positive and 38·5% were node positive. Lymphovascular invasion (LVI) was present in 24·3%. Of the 2, 686 women entered from 2002 onwards tested for HER2 status, 72·7% had a luminal tumour, 15·2% had a HER2+ tumour and 12·1% had a triple negative (TN) tumour. Results: Recurrence occurred in 459 (12·2%), predominantly in distant sites (71·7%). In women entered from 2002 onwards, the five and 10 year recurrence rates were significantly lower in the luminal group than the HER2+ and the TN groups. Few recurrences occurred in HER2+ and TN cancers after 36 months. On multivariate analysis the following were associated with a significantly increased risk of recurrence: nodal involvement (p < 0·0001), tumour grade (p < 0·0001), symptomatic presentation (p < 0·0001), presence of LVI (p = 0·001), non-luminal tumour type (p < 0·0001) and tumour size >50 mm (p = 0·02). Conclusion: The recurrence rate in this series was much lower than in previous older series. Lymph node involvement, tumour grade, symptomatic presentation, presence of LVI, non-luminal tumour type and tumour size (>50 mm) were associated with an increased risk of recurrence. We strongly recommend that clinicians include the presence of LVI and symptomatic presentation as well as the other established tumour factors, when assessing the risk of recurrence in women with EBC. Highlights: We analysed recurrence in 3, 765 Australian women with early breast cancer, treated between 1997–2015 with a median follow up of 83 months. Recurrence occurred in 459 (12.2%), predominantly in distant sites. Recurrence rates were significantly lower in the luminal than the HER2+ and triple negative groups. Nodal involvement, tumour grade, symptomatic presentation, lymphovascular invasion, negative tumour hormone receptor status and tumour size were associated with recurrence.